2022
DOI: 10.3390/antibiotics11121781
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Genomic Characterization of mcr-1-Harboring Escherichia coli Isolates from Chicken and Pig Farms in Lima, Peru

Abstract: Resistance to colistin generated by the mcr-1 gene in Enterobacteriaceae is of great concern due to its efficient worldwide spread. Despite the fact that the Lima region has a third of the Peruvian population and more than half of the national pig and poultry production, there are no reports of the occurrence of the mcr-1 gene in Escherichia coli isolated from livestock. In the present work, we studied the occurrence of E. coli carrying the mcr-1 gene in chicken and pig farms in Lima between 2019 and 2020 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…The mcr-1 gene was located between the nikB and pap2 genes and carried an IncI2 plasmid (Figure 1b). The nikB-mcr-1-pap2 structure is conserved among IncI2 plasmids, as previously reported in isolates from poultry in Peru [27] and other countries in Latin America [28]. The prevalence of positive isolates for the mcr-1 gene from pig samples has been reported in China (20.6%), Vietnam (22%), and Belgium (13.2%) [29][30][31].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The mcr-1 gene was located between the nikB and pap2 genes and carried an IncI2 plasmid (Figure 1b). The nikB-mcr-1-pap2 structure is conserved among IncI2 plasmids, as previously reported in isolates from poultry in Peru [27] and other countries in Latin America [28]. The prevalence of positive isolates for the mcr-1 gene from pig samples has been reported in China (20.6%), Vietnam (22%), and Belgium (13.2%) [29][30][31].…”
Section: Discussionsupporting
confidence: 71%
“…The prevalence of positive isolates for the mcr-1 gene from pig samples has been reported in China (20.6%), Vietnam (22%), and Belgium (13.2%) [29][30][31]. In Peru, a recent study found 12.5% (18/144) of isolates from pig farms positive for the mcr-1 gene [27].…”
Section: Discussionmentioning
confidence: 96%
“…IncI2 plasmids have been identified in several mcr-1 cases on various hosts worldwide [ 32 ], while the IncX4 plasmid type has been recognized as the primary carrier of the mcr-1 gene in isolates from healthy individuals in China [ 33 ], as well as in Enterobacteriaceae isolates carrying carbapenem and mcr-1 resistance genes simultaneously from clinical patients in Thailand [ 34 ]. Our study identified the presence of mcr-1 genes on both IncI2 and IncX4 plasmids, which have been recently observed in E. coli isolates from food, livestock, and humans across various countries [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 68%
“…We identified three bla CTX-M variants in our ESBL strains, with bla CTX-M-55 gene being the most common. Interestingly, recent surveillance studies have reported that this variant is also predominant in E. coli strains from pigs, cows, and chickens in Lima-Peru ( 43 , 44 , 50 ), suggesting that anthropogenic activities may serve as potential drivers of CTX-M-producing E. coli strains into the Amazonian wildlife. Conversely, bla CTX-M-15 and bla CTX-M-65 variants were found to a lesser extent in CTX-M-producing E. coli strains from livestock and bats in Peru ( 43 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent lineage in our dataset was the ST10 clone, a well-known high-risk pandemic lineage associated with infections in humans and has been found in livestock and meat in Peru (43,44) Other STs identified in this study, such as ST117, have been found in emerging ExPEC strains of foodborne E. coli, posing a risk to human health (45,46). ST752 has been associated with poultry in Europe and the United States and is considered predominant in chicken populations (47,48).…”
Section: Discussionmentioning
confidence: 99%